Effect of exercise on sleep quality and insomnia in middle-aged women: A systematic review and meta-analysis of randomized controlled trials - Rubio-Arias, Jacobo Á.; Marín-Cascales, Elena; Ramos-Campo, Domingo J.; Hernandez, Adrian V.; Pérez-López, Faustino R. (Maturitas, 2017)
•Low-moderate levels of exercise for 12 weeks had a positive effect on sleep quality.•Aerobic exercise had a positive effect on sleep quality, while low levels of physical activity (yoga) did not have a significant effect.•There was a non-significant reduction in the severity of insomnia. We assessed the effects of programmed exercise (PE) on sleep quality and insomnia in middle-aged women (MAW). Searches were conducted in five databases from inception through December 15, 2016 for randomized controlled trials (RCTs) evaluating the effects of PE versus a non-exercising control condition on sleep quality, sleep disturbance and/or insomnia in MAW. Interventions had to last at least 8 weeks. Sleep quality was assessed with the Pittsburgh Sleep Quality Index (PSQI) and insomnia with the Insomnia Severity Index (ISI). Random effects models were used for meta-analyses. The effects on outcomes were expressed as mean differences (MDs) and their 95% confidence intervals (CI). Five publications reported data from four RCTs on PE effects during 12–16 weeks on sleep quality (n=4 studies reporting PSQI results) and/or insomnia (n=3 studies reporting ISI results), including 660 MAW. Low-moderate levels of exercise significantly lowered the PSQI score (MD=−1.34; 95% CI −2.67, 0.00; p=0.05) compared with controls. In a subgroup analysis, moderate PE (aerobic exercise) had a positive effect on sleep quality (PSQI score MD=−1.85; 95% CI −3.62, −0.07; p=0.04), while low levels of physical activity (yoga) did not have a significant effect (MD-0.46, 95% CI −1.79, 0.88, p=0.50). In three studies (two studies of yoga, one study of aerobic exercise), there was a non-significant reduction in the severity of insomnia measured with the ISI score (MD −1.44, 95% CI −3.28, 0. 44, p=0.13) compared with controls. Heterogeneity of effects among studies was moderate to high. In middle-aged women, programmed exercise improved sleep quality but had no significant effect on the severity of insomnia.